A REVIEW OF THE ANTI-INFLAMMATORY AND ANTIMICROBIAL ACTIVITIES OF THE COMPONENTS OF THE CECROPIA GENUS - DAGA, MAIARA ALINE; AYALA, THAÍS SOPRANI; MENOLLI, RAFAEL ANDRADE (Asian Journal of Pharmaceutical and Clinical Research, 2020)
The genus Cecropia belongs to the Urticaceae family and has a wide diversity of species in several regions of South America. In folk medicine, they have many uses, such as hypoglycemic, antihypertensive, anti-inflammatory, and sedative. Species of the genus Cecropia, such as Cecropia pachystachya, Cecropia glaziovii, and Cecropia obtusifolia, have been the subject of several phytochemical studies, and the main isolated compounds were orientin, isoorientin, isovitexin, vitexin, as well as c-glycosylflavonoid compounds. These active compounds were characterized as responsible for the use of Cecropia plants in the treatment of inflammation and also as antimicrobial agents. This review aims to describe the main characteristics of the genus Cecropia, exploring the compounds responsible for the medicinal uses of these species and focusing on anti-inflammatory and antimicrobial uses.